Egg Shell Membrane as an Alternative Vascular Patch for Arterial Angioplasty - Sun, Peng; Yan, Shujie; Zhang, Liwei; Zhang, Cong; Wu, Haoliang; Wei, Shunbo; Xie, Boao; Wang, Xiaofeng; Bai, Hualong (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction: Egg shell membrane (ESM) is always considered as waste, but recent studies showed it has the potential to yield rapid reendothelialization in vitro. We hypothesized that ESM and heparin conjugated ESM (HESM) can be used as arterial patch in a rat aortic angioplasty model. Method: Sprague-Dawley (S-D) rat (200g) abdominal aortic patch angioplasty model was used. Decellularized rat thoracic aorta (TA) patch was used as control, ESM patch was made of raw chicken egg, heparin coated ESM (HESM) patch was made by using dopamine (DA); anticoagulation properties was verified in platelet adhesion tests; the TA patches, ESM patches and HESM patches were implanted to the rat aorta and harvested at day 14, samples were examined by immunohistochemistry and immunofluorescence. Result: The ESM patch showed a similar healing process like the TA patch, cells can migrate and infiltrate into both patches, there was a neointima with vWF positive endothelial cells, the endothelial cells acquire arterial identity with Ephrin-B2 and dll-4 positive cells; there were PCNA positive cells, PCNA and α smooth muscle Actin dual positive cells in the neointima in both groups. Heparin can be conjugated to the patch successfully and showed a strong anticoagulation property in vitro, HESM can also decrease mural thrombus formation after rat aortic patch angioplasty. Conclusion: ESM is a natural scaffold that can be used as vascular patch, it showed a similar healing process like decellularized TA patch, HESM showed anticoagulation property both in vitro and in vivo, ESM maybe a promising vascular graft in clinical.